Integrasi Servqual Kano Model dan Analisis SWOT Upaya Strategi Pemasaran untuk Peningkatan Kualitas Layanan pada CV Insani Production - Izzurromadlon, Achmad; Muhimatul Khoiroh, Siti (SURYA TEKNIKA, 2024)
CV. Insani Production is a business operating in the decoration rental sector which has been established since 1998. However, with the development of technology today, competition in the industrial world in the service sector has become increasingly intense, making competition in the service sector increasingly attractive. That way, his rivals are not only where he stands, and his rivals are no longer limited to a region, city, or even country. The resulting effect of this makes competition increasingly fierce between providers of event decoration and sound system rental services. So, it requires developing services not only to keep up with the times, but also to be able to compete in an era where all limited information no longer exists. CV. Insani Production experienced a decline in turnover due to a lack of development in service quality from year to year. Researchers help owners to overcome this by using the servqual, kano, and kansei engineering methods. Researchers use this method to find out what customers really want, so they can fulfill customers' current needs.